In Vivo Evaluation of PVP-Gelatin-Chitosan Composite Blended with Egg-Yolk Oil for Radiodermatitis - Yi-Chi Hung (MDPI AG, 2021)
Radiation-induced skin injury (RSI) is a frequent complication of radiotherapy. Severe cases affect the patient’s disease treatment and quality of life. The main purpose of this study is to examine the causative role of egg-yolk oil (EYO) in delayed radiation-induced skin injury, including impaired wound healing. Using polyvinyl pyrrolidone (PVP)-gelatin-chitosan (PGC) composite film as controlled release of egg-yolk oil (EYO) was studied in rats, which were used as a radiation-induced skin injury model. Different composition ratios were tested for their mechanical properties, moisture content, and degradation characteristics. The results showed that the PGC112 (w/w) substrate, which will hence be referred to as PGC, had the better properties. Further, the PGC was mixed with EYO (0.25% and 0.5%) to prepare the films (PGC/0.25EYO and PGC/0.5EYO, respectively). Furthermore, the mechanical and degradation properties and biocompatibility showed better results with PGC/0.5EYO. In animal studies, rats were irradiated with single-dose electron beams of 40 Gy. The animals were divided into five groups to perform wound treatment with various types of wound dressing for 30 days. Histological examination and CD68 immunochemical staining were then conducted, and observations were made. The results showed that PGC/0.5EYO has a significantly healing effects on radiodermatitis and good re-epithelialization.